Território no mundo A’uwe Xavante - Maria Lucia Cereda Gomide (Confins, 2011)
This objective of this article is to discussthe conception of territory and territoriality of the A’uwe Xavante people. The geographical boundaries of this research are the Xavante indigenous land in the east of Mato Grosso. These people have today a population of around 14.000 people, distributed in nine Indigenous lands (TI):  Sangradouro, São Marcos, Areões, Pimentel Barbosa. Parabubure, Chão Preto, Ubawawe, Marechal Rondon, Marãiwatsede. This people has been marked by the migrations in the savannas of central-west Brazil, where they tried to live without contact with the surrounding society, but with the occupation of the region by the Brazilian State, principally with the “westwards march” in the 1930s, resulted in an invaded et enclosed indigenous territory, thus creating grave conflicts and leading to the demarcation of the Xavante indigenous territory in the 1970s. This research deals with the Xavante territory and territoriality. Is well known that physical and cultural reproduction of the indigenous people are closely conditioned by territory delimitation, which must take into account the territoriality and the indigenous way of life. That was not the case for the Xavante territory.The delimitation of the Xavante indigenous territory in many "islands" caused various social and environmental problems, changing their way of life. To rebuild the indigenous territory that was wrongly and intentionally fragmented and divided in islands is a great political challenge for the Xavante people.The indigenous territory includes the relations of the space appropriation, which has different aspects such as politial, symbolic and cosmologic for each indian tribe. On the other hand, the indigenous land is a category created by the legal-political process of the State. Therefore a conflict arises from the contact between the indigenous people and the surrounding society, since there are different spatial logics in confrontation.